2022
DOI: 10.1111/jonm.13869
|View full text |Cite
|
Sign up to set email alerts
|

Integrating sustainability development education program in nursing to challenge practice among nursing interns in health care

Abstract: Aim: This study aimed to investigate the Integrating Sustainability Development Education Program in Nursing to Challenge Practice Among Nursing Interns in Health Care. Background: The combination of sustainable development and climate change in health care delivery benefits from the apparent environmental changes. Subjects and Methods: The quasi-experimental, cross-sectional, comparative study included 160 nursing interns who completed the intervention. Both genders were assigned to Saudi (N = 80) and Egyptia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
3
0
0
Order By: Relevance
“…Thus, they might need to find it more worthy of attention. Similar results have been observed in previous studies conducted in Egypt [ 36 , 37 ]. This trend is not unique to Egypt, as studies on university students in Spain [ 53 ], Sweden [ 54 ], and India [ 49 ] have reported similar results.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, they might need to find it more worthy of attention. Similar results have been observed in previous studies conducted in Egypt [ 36 , 37 ]. This trend is not unique to Egypt, as studies on university students in Spain [ 53 ], Sweden [ 54 ], and India [ 49 ] have reported similar results.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the students in this study expressed less favorable attitudes while simultaneously demonstrating a higher level of engagement in environmentally sustainable behaviors. This finding aligns with previous studies indicating that nursing students exhibited the highest scores for sustainability behavior in the environmental dimension, followed by the social dimension, while the economic dimension received the lowest scores [ 36 , 50 ]. The complex and global nature of environmental sustainability issues, particularly those related to climate change and pollution, has received significant attention in both the global and Egyptian media.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…to modern luxury establishments, hotels have played a crucial role in accommodating travellers and providing a temporary home away from home (Chang & Cheng, 2019;Moustafa Saleh & Elsabahy, 2022). This article will take you on a journey through the evolution of the hotel industry, highlighting key milestones and developments along the way.…”
mentioning
confidence: 99%